1998
DOI: 10.1243/0954406981521277
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and finite element studies of the running of V-ribbed belts in pulley grooves

Abstract: A finite element model of a complete loop of V-ribbed belt running between two torque transmitting pulleys has been created to study the mechanics of contact between a belt rib and pulley groove. It has been validated against experimental measurements of radial movement of a K-section belt running on 80 mm diameter pulleys. Patterns of sticking and slip between the belt and pulley are predicted. Of particular interest are the patterns of traction in entry and exit regions and, in fully seated regions, the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 11 publications
(4 reference statements)
0
13
0
Order By: Relevance
“…8-10 was executed in the following sequence. First step is to geometrically position the designated pulley inside the unstretched circular shaped belt, which was then loosely wrapped onto the pulley as done by Lawrence et al [1] and Yu et al [3]. A concentrated force is then applied to pulley reference node and meanwhile the ends of the belts are constrained.…”
Section: Dynamic Simulation Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…8-10 was executed in the following sequence. First step is to geometrically position the designated pulley inside the unstretched circular shaped belt, which was then loosely wrapped onto the pulley as done by Lawrence et al [1] and Yu et al [3]. A concentrated force is then applied to pulley reference node and meanwhile the ends of the belts are constrained.…”
Section: Dynamic Simulation Proceduresmentioning
confidence: 99%
“…A current survey of belt literature revealed that many investigations addressed nonlinear laminated fiber reinforced elastomer mechanics [1][2][3][4][5], but no useable model was found with adequately detailed three-dimensional computations necessary to distinguish rib to rib stress variation required for misalignment analysis. Connell and Rorrer [6] demonstrated that proper control of belt-pulley tracking parameters reduced noise generated from belt-pulley systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1) consists of an elastomer or a fabric backing, a layer of polyester cords in a protective cushion elastomer compound and the rib elastomer compound. Yu et al [1] presented a comprehensive study of the belt moving in pulley grooves. A three-dimensional finite element model represented a complete half rib operating between two pulleys.…”
Section: Introductionmentioning
confidence: 99%